INVESTIGATING THE QUALITY OF WATER STORED IN PLASTIC TANKS IN UMARU MUSA YAR’ADUA UNIVERSITY KATSINA, KATSINA STATE, NIGERIA - HASSAN, MUDASSIR; Hussaini, A.; Musa, A.; Muhammad, M. (FUDMA JOURNAL OF SCIENCES, 2021)
Water is one of the most important natural resources which play an essential role in human life. Most of the Nigerian institutions stored water in either plastic or overhead tanks for different purposes. However, there has been a growing concern over the safety of the stored water for human consumption following reported cases of microbial occurrence in water stored in tanks. This study aimed at investigating the water quality stored in plastic tanks in Umaru Musa Yar’adua University Katsina. Water samples were collected from plastic tanks and analyzed for some physico-chemical and heavy metals parameters. The result of physico-chemical parameters obtained shows that only dissolved oxygen, biological oxygen demand and chemical oxygen demand were observed above the maximum permissible limit for drinking recommended by WHO and NSDWQ with the mean value of 55.18 mg/l, 38.86 mg/l and 38.08 mg/l respectively. While the remaining parameters such as pH, electrical conductivity, total dissolved solids, turbidity, total suspended solid, alkalinity, sulphate, nitrate, phosphate, chloride and total hardness were found within the acceptable limit. However, analyzed result of heavy metals parameters revealed that all parameters were observed within desirable limit by WHO and NSDWQ for drinking water and suggested that the quality of water stored in plastic tanks was very good. It is concluded that, the quality of water stored in plastic tanks is suitable for human consumption. It is therefore recommended that, continuous monitoring of the water should be maintain so as to ascertain the safety of the water